Perspektif Kajian Media Digital pada Performa Seni Jepang di Instagram @performance.jpa - Susilo, Daniel; Putranto, Teguh Dwi; Garcia, Erica Monica A. (Ayumi : Jurnal Budaya, Bahasa, dan Sastra, 2021)
The use of digital media to promote local culture has become a new breakthrough in exposing local culture to international countries. In addition to being able to be immediately recognized in other nations, digital media promotion is also less expensive and quicker to implement. This study aims to determine the perspective of Digital Media Studies in Japan Performing Arts. The method used in this research is Krippendorff content analysis on Instagram @performance.jpa by using Japanese dance indicators which include Kabuki, Kasa Odori, Bon Odori, Noh Mai, Onikenbai, Nanazumai, Wadaiko, Arauma, Nihon Buyo. The conclusion of this study shows that Japan Performing Arts introduces Japanese culture through the collaboration of western culture by promoting the Nihon Buyo dance.